The application of eye movement desensitization and reprocessing treatment (EMDR) on adults with foreign language anxiety - Toprak-Yildiz, Tugba Elif; Colak, Tugba Seda; Koc, Mustafa; Dusunceli, Betul (Language learning in higher education (Berlin, Germany), 2021)
The present study aimed to apply Eye Movement Desensitization and Reprocessing (EMDR) treatment to foreign language (FL) anxiety, a complex and multidimensional phenomenon that has been found to exert profound effects on many aspects of FL learning and performance. EMDR originally emerged as a treatment for post-traumatic stress disorder (PTSD), and a great number of studies demonstrated empirically its potential for treating and coping with various psychological disorders. The present study used the Single-Case Design (SCD). EMDR was given to two volunteer adult EFL (English as a Foreign Language) learners experiencing severe FL anxiety. The effect of the treatment on FL anxiety was tracked and measured by using two separate scales of FL anxiety and obtaining self-reports of distress from the subjects. The long-term effects of EMDR were checked through two separate follow-up assessments. The results clearly demonstrated that EMDR was effective in reducing FL anxiety and increasing subjects’ positive cognition.